Plasma prolactin concentrations following epileptic and pseudoseizures. Issue 6 (June 1983) - Collins, W C; Lanigan, O; Callaghan, N
Abstract : Serial plasma prolactin levels were measured following eighteen generalised seizures, ten partial seizures and eight pseudoseizures. Prolactin levels were elevated following generalised seizures, but were normal following the other seizure types. Plasma prolactin levels may, therefore, be helpful in differentiating between generalised and pseudoseizures. The optimal time for estimating the prolactin level was 15-20 minutes following the seizure.